2016
DOI: 10.1139/gen-2015-0101
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA polymorphism in the indica rice varieties RGD-7S and Taifeng B as revealed by whole genome re-sequencing

Abstract: Next-generation sequencing technologies provide opportunities to further understand genetic variation, even within closely related cultivars. We performed whole genome resequencing of two elite indica rice varieties, RGD-7S and Taifeng B, whose F1 progeny showed hybrid weakness and hybrid vigor when grown in the early- and late-cropping seasons, respectively. Approximately 150 million 100-bp pair-end reads were generated, which covered ∼86% of the rice (Oryza sativa L. japonica 'Nipponbare') reference genome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…These regions of the genes are mainly involved in the regulation of gene expression, so these changes might be involved in changes in gene expression. Similar results were previously reported for significant genetic polymorphism in the genomes of indica rice varieties RGD-7S and Taifeng B, whose F 1 progeny exhibited the hybrid weakness phenotype (Fu et al , 2016). Overall, these results indicated that the genetic backgrounds of these japonica rice varieties were very different and that they might have originated and evolved under very different conditions.…”
Section: Discussionsupporting
confidence: 90%
“…These regions of the genes are mainly involved in the regulation of gene expression, so these changes might be involved in changes in gene expression. Similar results were previously reported for significant genetic polymorphism in the genomes of indica rice varieties RGD-7S and Taifeng B, whose F 1 progeny exhibited the hybrid weakness phenotype (Fu et al , 2016). Overall, these results indicated that the genetic backgrounds of these japonica rice varieties were very different and that they might have originated and evolved under very different conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Next-generation sequencing technologies have enabled re-sequencing of massive genomes, detection of DNA variations, and development of polymorphic molecular markers (Weigel and Mott 2009 ; Huang et al 2012 ). The previous studies have reported the polymorphisms in genomic sequences of diploid rice, and discovered abundant genetic variations and important mutant genes (Jain et al 2014 ; Fu et al 2016 ). In the present study, a total of 82 SNPs and 182 InDels were detected in autotetraploid rice compared to diploid rice, and only three non-synonymous SNPs and six large-effect InDels were identified, which were associated with three and six genes/proteins, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have concentrated on the analysis of genes associated with heading date and grain-related traits using whole-genome re-sequencing (Huang et al 2012 ). Fu et al ( 2016 ) identified numerous SNPs and InDels in two indica rice (RGD-7S and Tai Feng B) and obtained DNA polymorphic markers by re-sequencing two rice cultivars. RNA transcript technology (RNA-seq) is a helpful tool for understanding of differentially expressed genes and the expression patterns of stage-specific genes in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The observed genome polymorphisms were mainly located in intergenic, upstream, and downstream regions, and similarities were observed among the genotypes (Table 3). Changes in these regions may influence gene expression, but not gene function [36]. Regarding the substitution of bases, the transition to transversion ratio (Ti/Tv) observed in the four varieties was 1.45 in our study.…”
Section: Discussionmentioning
confidence: 46%